Oxalic acid enhances bioremediation of Cr(VI) contaminated soil using Penicillium oxalicum SL2. (January 2023) - Long, Bibo; Liao, Lingling; Jia, Fei; Luo, Yating; He, Junyu; Zhang, Wenhua; Shi, Jiyan
Abstract: Oxalic acid is the most abundant low molecular weight organic acid (LMWOA) in many environments and offers enormous prospects for treating Cr(VI) contamination. In this study, laboratory batch experiments were conducted to estimate the roles of oxalic acid in Cr(VI) removal by Penicillium oxalicum SL2. Oxalic acid changed the initial pH and provided a suitable condition for the growth of strain SL2 when the penicillium was applied to bioremediation of Cr(VI) contamination in alkaline soil. Gompertz model analysis indicated that initial pH affected the lag time of the growth curve of strain SL2. Scanning electron microscopy and scanning transmission X-ray microscopy analysis showed strain SL2 sufficiently contacted with contaminated soil and reduced Cr(VI) to Cr(III) in the hyphae. The results suggested that oxalic acid could enhance the bioremediation efficiency of strain SL2 though improving chromium bioleaching from the contaminated soil and strengthening Cr(VI) removal in the leaching solution. This study provided oxalic acid as a green reagent for stimulating Cr(VI) removal by strain SL2 and would expand knowledge on the roles of LMWOA in Cr(VI) bioremediation. Graphical abstract: Image 1 Highlights: Gompertz model could simulate the growth curve of strain SL2 under initial pH5 to pH9. Growth of strain SL2 had a strong correlation with Cr(VI) removal. Oxalic acid improved chromium bioleaching by strain SL2 from contaminated soil. Oxalic acid enhanced Cr(VI) removal by strain SL2 in the leaching solution.